Improving Teacher Ability in Preparing HOTS Questions Through Workshop Activities at Kebonharjo Public Elementary School Kapanewon Samigaluh Kulon Progo for the 2021/2022 Academic Year - Wakijem Wakijem (International Journal of Chemistry Education Research, 2022)
The purpose of this research is to see the teacher's ability in preparing HOTS questions during the workshop and also to see the ability of the presenters in delivering material with the theme of HOTS-based question preparation at SD Negeri Kabonharjo Samigaluh. The research method used is School Action Research. The research was carried out in two cycles, each cycle consisting of planning, implementing actions, observing, and reflecting. The subjects of this study were teachers at SD Negeri Kabonharjo, Samigaluh in the 2021/2022 academic year. The results showed that the ability of teachers in preparing HOTS-based questions increased from each cycle (I and II), this indicates that workshop activities have great benefits in terms of improving the ability of teachers in preparing questions. Furthermore, the ability of the presenters in presenting the material for the preparation of Higher Order Thinking Skills (HOTS) questions also increased every cycle, meaning that the presenters had good abilities in delivering material in workshop activities